Brain injury in neonatal incontinentia pigmenti: the role of multimodality neuroimaging. (12th May 2016) - Poretti, Andrea; Northington, Frances J
Abstract : This commentary is on the original article by Soltirovska Salamon et al. on pages1076–1084 of this issue.